MBRS-32. METHYLATION PROFILE IN A RETROSPECTIVE SERIES OF SPANISH PEDIATRIC MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Martin-Guerrero, Idoia; Aurtenetxe, Olaia; Zaldumbide, Laura; Astigarraga, Itziar; Hicks, Debbie; Schwalbe, Ed; Clifford, Steve; Garcia-Ariza, Miguel; Navajas, Aurora
Abstract: PURPOSE: Consensus molecular subgroups of Medulloblastoma (MB), namely WNT, SHH, Group 3 and Group 4, exhibit divergent biology and clinical outcomes. To date optimal ways of identifying MB subtypes are based on the analysis of transcriptional and epigenetic signatures. The present study aimed to examine clinical and molecular correlates of the MB consensus subgroups in a large retrospective series of Spanish MB samples. METHODS: The study population included 86 MB patients (age <16 years at diagnosis) recruited from 18 Spanish hospitals since 1997 to 2015. The 45% of patients were classified as high risk and the 55% as standard risk. DNA methylation profiles were generated from 57 FFPE and 29 frozen tumoral tissues (66.3% FFPE and 33.7% frozen) using the Illumina Methylation EPIC Array. Clinical data including follow-up were collected. All patients were treated following SIOP collaborative brain tumor protocols. RESULTS: Preliminary results show that, according to the methylation profile, our series include patients belonging to WNT group (≈8%), SHH (≈24%), Group 3 (≈24%) and Group 4 (≈29%). The 86% of WNT tumors display classic histology, while the 68% of SHH group are desmoplastic/nodular. Group 3 and 4 mainly show classic histology (67 and 84%, respectively). Remarkably, the 56% of MYCC positive patients are included in the Group 3. CONCLUSION: The study of DNA methylation profiling in a Spanish MB series has enabled the molecular classification of MB samples, improving disease-risk stratification. This project was supported by Asociación Pablo Ugarte and Pequeropa.